Efeitos do treinamento em natação sobre propriedades mecânicas e estruturais do fêmur de ratas ovariectomizadas - Fernandes, Barbara Braga; Del Carlo, Ricardo Junqueira; Gouveia Peluzio, Maria do Carmo; Drummond, Lucas Rios; Osorio Silva, Carlos Henrique; Louzada, Mário Jefferson Quirino [UNESP]; Freitas, Juliana Silveira; Castro, Cynthia Aparecida; Silva, Karina Ana; Natali, Antonio Jose (Univ Federal Uberlandia, 2014)
We investigated the effects of swimming training (ST) on femoral mechanical and structural properties in ovariectomized female rats. Female Wistar rats [age = 20 weeks; body weight (BW) = 271,42 +/- 17,6 g] were subjected to ovariectomy (OVX) or laparotomy (SHAM) and allocated to one of the following groups: swimming OVX (SO, n=12), control OVX (CO, n=12), swimming SHAM (SS, n=12) and control SHAM (CS, n=12). Fifteen days after surgery SO and SS groups were subjected to a ST (60 min/day, 5 days/week, overload of 3% of BW) for 10 weeks. Alkalin phosfatase was reduced in OVX as compared to SHAM (18,87 pg/mL vs. 53,93 pg/mL, respectively), but not altered by ST. Animals SHAM showed more cancellous bone than OVX (255,50 +/- 38,27 vs 288,75 +/- 39,63 points, respectively). Exercised animals exhibited more cancellous bone than controls (292,00 +/- 33,54 vs 251,54 +/- 38,99 points, respectively) in this region and in the grater trochanter (281,50 +/- 34,42 vs 237,23 +/- 53,03 points; respectively). Bone mineral density and cortical bone in the femur midshaft were not altered either by OVX or ST. The maximum force and thoughness of the femoral neck and midshaft were not affected either by OVX or ST. It was concluded that ST benefits cancellous bone mass in the femoral proximal region (i.e. femoral neck and greater trochanter), independently of ovariectomy, which did not reflect in improved mechanical properties either in the femoral neck or midshaft.
Effects of swimming training on femoral mechanical and structural properties in ovariectomized female rats
Keywords: Physical exercise; Osteopenia; Bone fracture